Pediatric Liver Transplant Recipients Who Undergo Transfer to the Adult Healthcare Service Have Good Long‐Term Outcomes. Issue 7 (23rd February 2015) - Sagar, N.; Leithead, J. A.; Lloyd, C.; Smith, M.; Gunson, B. K.; Adams, D. H.; Kelly, D.; Ferguson, J. W.
<x xml:space="preserve">Abstract</x> Liver transplantation has transformed survival for children with liver disease necessitating the transfer of a growing number of patients to the adult healthcare service. The impact of transfer on outcomes remains unclear. The aim of this single‐center study of 137 consecutive pediatric liver transplant recipients was to examine the effect of transfer on patient and graft survival. The median time from transplant to transfer was 10.4 years and the median age of the patients at transfer was 18.6 years. After transfer, there were 5 re‐transplants and 12 deaths in 14 patients. The estimated posttransfer 10‐year patient and graft survival was 89.9% and 86.2%, respectively. Overall, 4 patients demonstrated graft loss as a consequence of chronic rejection. Graft loss was associated with older age at first transplant (p = 0.008). When compared to young adult patients transplanted in the adult center, the transferred patients did not have inferior graft survival from the point of transfer (HR 0.28; 95% CI 0.10–0.77, p = 0.014). This suggests that transfer did not impact significantly on graft longevity. In conclusion, pediatric liver transplant recipients who undergo transfer to the adult service have good long‐term outcomes.